In situ growth experiments of reef-building cold-water corals: The good, the bad and the ugly. (March 2017) - Lartaud, F.; Meistertzheim, A.L.; Peru, E.; Le Bris, N.
Abstract: The ecological study of corals in their habitat is essential to determine the effects of global change and to develop strategies for reef conservation. Based on mark and recovery experiments, we investigated skeletal growth patterns of two reef-building cold-water coral species, Lophelia pertusa and Madrepora oculata, in the Lacaze-Duthiers canyon in the northwestern Mediterranean Sea. Coral fragments were collected, stained and deployed for short-term (2.5 months) and long-term (15 months) growth experiments at two sites located 4.5 km and 6.8 km from the canyon head. The analysis of distinct growth parameters (budding, new polyp growth and linear extension of the coral fragments) revealed that growth patterns are consistent among branches of different sizes, but discrepancies arose from the different types of staining used. Calcein appeared more suitable than alizarin red, which strongly limited growth by delaying coral recovery, for short-term experiments at least. Both species grew rapidly when redeployed in their habitat. Effects of long-term experiments could not be observed because corals were exposed to harmful environmental stress, particularly the lethal effect of sedimentation on the fragments. Despite limited in situ deployment, the growth analysis from the short-term experiment highlighted species-specific responses according to the location along a longitudinal gradient in the canyon and were likely related to the local environmental conditions. Consistent with the observed species distributions, M. oculata showed optimal growth at the site closer to the canyon head compared with L. pertusa, which had optimal growth at the deeper site. In situ experiments are difficult to conduct in deep-sea ecosystems, but with the use of remotely operated vehicles (ROVs), such a simple approach may be of interest to managers of cold-water coral ecosystems. Highlights: We examine different methodological tools to analyse in situ growth of deep corals. The type of staining impacts the coral growth, not the size of coral fragments. High sedimentation rates limit growth due to strong polyp mortality. Species-specific responses depending locations suggest different ecological niches.